2009
DOI: 10.1007/s00431-009-1102-1
|View full text |Cite
|
Sign up to set email alerts
|

Prolidase deficiency: it looks like systemic lupus erythematosus but it is not

Abstract: Three siblings with recalcitrant leg ulceration, splenomegaly, photosensitive rash, and autoantibodies were suspected of having prolidase deficiency. Urine was checked for iminodipeptiduria, fibroblasts were cultured and analyzed for prolidase activity, and DNA was extracted for identifying the causative mutation. Glycyl proline was found as the dominant dipeptide in the urine. The activity of proline dipeptidase in fibroblasts was 2.5% of control fibroblasts. Sequence analysis of the PEPD gene revealed a homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…For this reason, the carbohydrate-deficient transferrin studies were tested and found negative, ruling out congenital disorders of glycosylation. Notably, SLE has been linked to PD [Bissonnette et al, 1993;Shrinath et al, 1997;Di Rocco et al, 2007] and is associated with multiple mutations [Lupi et al, 2006[Lupi et al, , 2008Falik-Zaccai et al, 2010;Klar et al, 2010;Butbul Aviel et al, 2012]. The mechanistic relationship between these entities is not clear, but a loss of immune tolerance to lupus-associated autoantigens in PD has been hypothesized, leading to positive antinuclear antibodies and other autoantibody testing even in patients without clinical SLE [Kurien et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, the carbohydrate-deficient transferrin studies were tested and found negative, ruling out congenital disorders of glycosylation. Notably, SLE has been linked to PD [Bissonnette et al, 1993;Shrinath et al, 1997;Di Rocco et al, 2007] and is associated with multiple mutations [Lupi et al, 2006[Lupi et al, , 2008Falik-Zaccai et al, 2010;Klar et al, 2010;Butbul Aviel et al, 2012]. The mechanistic relationship between these entities is not clear, but a loss of immune tolerance to lupus-associated autoantigens in PD has been hypothesized, leading to positive antinuclear antibodies and other autoantibody testing even in patients without clinical SLE [Kurien et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…It splits imidodipeptides with Cterminal proline or hydroxyproline, making proline available for reutilization in collagen synthesis [Myara et al, 1984;Klar et al, 2010]. In PD, this enzyme has decreased or complete loss of activity, giving rise to imidodipeptiduria and a variety of clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that an association might have been between prolidase defi ciency and systemic lupus erythematosus (SLE) in literature (9,15). Prolidase defi ciency could be a risk factor for the development of SLE.…”
Section: Prolidase Defi Ciencymentioning
confidence: 99%
“…Some human pathologies have been associated with prolidase. For example, a lack of prolidase activity causes an autosomal recessive disorder, prolidase deficiency (PD), occurring in one to two per million births (Endo et al, 1990;Klar et al, 2010). This disorder is characterized by chronic ulcerative dermatitis, mental retardation, frequent infections, and massive urinary excretion of imidodipeptides (Buist, Strandholm, Bellinger, & Kennaway, 1972;Endo, Matsuda, Ogata, & Tanaka, 1982;Goodman et al, 1968;Kodama et al, 1976;Nakayama et al, 2003;Powell, Rasco, & Maniscalco, 1974;Sheffield, Schlesinger, & Paull, 1997;Uramatsu et al, 2009).…”
mentioning
confidence: 99%